Pengaruh Public Speaking dan Good Looking Terhadap Kinerja Staff Marketing Visigo Academy Aceh - Akmal, Nailatul; Fadhillah, Is (Ikatan Da'i Indonesia, 2024)
Competition between businesses between companies is getting tighter, public speaking skills and good looking are considered important in the world of work. This study aims to find out more about “The influence of public speaking and good looking on the performance of marketing staff Visigo Academy Aceh. Public speaking and good looking skills have an important role in the performance of marketing staff in every company. This research uses quantitative methods and questionnaire surveys distributed to all students of Visigo Academy Aceh. The results showed that most students of Visigo Academy Aceh agreed that public speaking and good looking affect the performance of marketing staff. Therefore, it can be concluded that public speaking and good looking affect the performance of marketing staff of Visigo Academy Aceh.